ANALISIS SWOT SEBAGAI LANDASAN STRATEGIS PENINGKATAN DAYA SAING PADA BLUE BIRD GROUP - Rahmadina, Dean Seshar; Azzatillah, Azzatillah; Triandri, Urip; Riansyah, Ananda Adi (Jurnal Investasi, 2024)
The goal of this study is to find both internal and external factors that affectcompetitiveness of Blue Bird Group, one of Indonesia's leading transportation companies, using SWOT analysis. Through a qualitative approach, this research collected data via interviews, observations, and documentary studies. The SWOT analysis results indicate that Blue Bird's main strengths are its strong brand image and extensive network, while its primary weakness is dependence on the domestic market. Opportunities that can be leveraged include expansion into online transportation services, and the threats faced are intense competition from ride-sharing companies. Based on these findings, this study recommends several strategies to enhance the competitiveness of Blue Bird Group, including service diversification and the development of digital innovations. This research provides strategic insights for Blue Bird in maintaining and enhancing its position in the dynamic transportation industry.